Characterization of Pseudomonas aeruginosa Bacteriophage L5 Which Requires Type IV Pili for Infection - Yang, Lan; Zhang, Tingting; Li, Linlin; Zheng, Chao; Tan, Demeng; Wu, Nannan; Wang, Mingyang; Zhu, Tongyu (Frontiers in Microbiology, 2022)
Pseudomonas aeruginosa is a common opportunistic human pathogen. With the emergence of multidrug-resistant (MDR) clinical infection of P. aeruginosa, phage therapy has received renewed attention in treating P. aeruginosa infections. Moreover, a detailed understanding of the host receptor of lytic phage is crucial for selecting proper phages for therapy. Here, we describe the characterization of the P. aeruginosa bacteriophage L5 with a double-stranded DNA genome of 42,925 bp. The genomic characteristics indicate that L5 is a lytic bacteriophage belonging to the subfamily Autographividae. In addition, the phage receptors for L5 were also identified as type IV pili, because the mutation of pilZ, which is involved in pili synthesis, resists phage infection, while the complementation of pilZ restored its phage sensitivity. This research reveals that L5 is a potential phage therapy candidate for the treatment of P. aeruginosa infection.